Features of the mathematical model of the interaction between track and rolling stock within the switch - Rybkin, V. V.; Kalenyk, K. L. (Science and Transport Progress, 2009)
In this work the peculiarities of mathematical modeling of interaction of rail vehicles and switches when moving onto a side track are given. The mathematical model of interaction taking into account the given peculiarities of switch side direction is developed and approved.